2013
DOI: 10.1111/cei.12187
|View full text |Cite
|
Sign up to set email alerts
|

Dimorphic HLA-B signal peptides differentially influence HLA-E- and natural killer cell-mediated cytolysis of HIV-1-infected target cells

Abstract: SummaryAs a mechanism of self-protection, signal peptides cleaved from human leukocyte antigen (HLA) class I products bind to HLA-E before the complex interacts with the natural killer (NK) cell receptor CD94/NKG2A to inhibit NK-mediated cell lysis. Two types of the signal peptides differ in their position 2 (P2) anchor residue, with P2-methionine (P2-M) having higher HLA-E binding affinity than P2-threonine (P2-T). All HLA-A and HLA-C molecules carry P2-M, whereas HLA-B products have either P2-M or P2-T. Epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 41 publications
2
39
1
1
Order By: Relevance
“…It seems likely that both processes act in synergy to build functional potential in the NKG2A + NK cell subset, similar to what has been observed for KIR-mediated education in self KIR + CD57 + NK cells (19). Notably, the strength of the NKG2A-HLA-E interaction is determined by dimorphism in the HLA-E leader sequence peptide at position 2 (P2) (methionine versus threonine) and significantly influences the missing self response of NKG2A + NK cells (24,25). The link between inhibitory receptor input (through NKG2A) and function suggests that education plays an important role in shaping the responsiveness of the NKG2A + NK cell subset.…”
Section: Nkg2asupporting
confidence: 54%
“…It seems likely that both processes act in synergy to build functional potential in the NKG2A + NK cell subset, similar to what has been observed for KIR-mediated education in self KIR + CD57 + NK cells (19). Notably, the strength of the NKG2A-HLA-E interaction is determined by dimorphism in the HLA-E leader sequence peptide at position 2 (P2) (methionine versus threonine) and significantly influences the missing self response of NKG2A + NK cells (24,25). The link between inhibitory receptor input (through NKG2A) and function suggests that education plays an important role in shaping the responsiveness of the NKG2A + NK cell subset.…”
Section: Nkg2asupporting
confidence: 54%
“…Furthermore, positions 67 and 116 (and to a lesser extent position 97) of the HLA-B antigen-binding groove are critical determinants of the binding specificity of some HLA-B alleles for KIR3DL1 or KIR3DS1 receptors (22). Beyond the MHC-I antigen-binding groove, we identified an association between BD and a variant of the HLA-B signal peptide that independently regulates CTL and NK-cell activation through HLA-E and the C-type lectin-like heterodimeric receptors, CD94/NKG2 (34)(35)(36). Coincidentally, we previously have identified an association between BD and KLCR4, which encodes the C-type lectin-like receptor, NKG2F (6).…”
Section: Discussionmentioning
confidence: 93%
“…Uninfected partners of T/T genotype were more resistant to infection, than uninfected partners of either M/T or M/M genotype. Moreover, the NKG2A + NK cells from uninfected T/T partners were more effective at killing autologous HIV-infected target cells in vitro , than the NKG2A + NK cells of uninfected M/T or M/M partners (7, 8). Here the effect of -21M is dominant and -21T is subordinate, the hierarchy observed throughout our analysis.…”
Section: Discussionmentioning
confidence: 95%
“…Subsequent appreciation that Bw4 correlates with -21T HLA-B led to a reanalysis of the clinical data which showed that the beneficial effects correlate well with -21T HLA-B homozygosity (9). Thus the correlation with Bw4 homozygosity can also be interpreted in terms of a mechanism involving HLA-E recognition by the CD56 dim CD94:NKG2A + cells of T/T donors, NK cells known to be effective against HIV (7, 8). Thus the protection associated with Bw4 + HLA-B homozygosity could be mediated by KIR3DL1 + cells or CD94:NKG2A + cells, or by their combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation